2022
DOI: 10.1038/s41420-022-01030-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia induces gastric carcinoma proliferation and migration via the Pin1/BRD4 pathway

Abstract: Diabetes is a potential risk factor for gastric cancer (GC). Pin1, a peptidyl–prolyl cis/trans isomerase, promotes GC cell proliferation and migration. The role and underlying mechanism of the Pin1/BRD4 axis in hyperglycemia-induced proliferation and migration of GC cells were analyzed in vivo and in vitro. Proliferation and migration of GC cells were measured; Pin1 and BRD4 expression of the cell cycle were determined. Pin1 and BRD4 were downregulated by transfecting Pin1 shRNA lentivirus into GC cells and JQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“… 28 Hyperglycemia also enhances gastric carcinoma proliferation and migration via thr Pin1/BRD4 transcriptional pathway, involved in the hyperglycemia‐induced inflammatory process. 29 Second, H. pylori infection, a known risk factor for gastric cancer, is maintained in hyperglycemia, allowing the bacteria to grow and survive longer in patients with diabetes. 30 An in vitro study reported enhanced adhesion, growth, and viability of the H. pylori cytotoxin‐associated gene A antigen, an oncoprotein, under higher glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 Hyperglycemia also enhances gastric carcinoma proliferation and migration via thr Pin1/BRD4 transcriptional pathway, involved in the hyperglycemia‐induced inflammatory process. 29 Second, H. pylori infection, a known risk factor for gastric cancer, is maintained in hyperglycemia, allowing the bacteria to grow and survive longer in patients with diabetes. 30 An in vitro study reported enhanced adhesion, growth, and viability of the H. pylori cytotoxin‐associated gene A antigen, an oncoprotein, under higher glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…First, insulin and hyperglycemia may directly promote gastric cancer by overstimulating tumorigenic pathways such as PI3K/AKT/mTOR, 27 insulin‐like growth factor‐1 (IGF‐1), strongly linked to insulin resistance, promotes gastric cancer cell proliferation and invasion via the Ras/RAF/MEK/ERK and JAK1/STAT3 cellular signaling pathways 28 . Hyperglycemia also enhances gastric carcinoma proliferation and migration via thr Pin1/BRD4 transcriptional pathway, involved in the hyperglycemia‐induced inflammatory process 29 . Second, H. pylori infection, a known risk factor for gastric cancer, is maintained in hyperglycemia, allowing the bacteria to grow and survive longer in patients with diabetes 30 .…”
Section: Discussionmentioning
confidence: 99%
“…These reports showed that NAP1L1 has multiple functions beyond the nucleosome assembly function. Such functions include proliferation, migration, invasion, and even thrombopoiesis (Freitag & Schwertz, 2022; Liang et al, 2022; Nagashio et al, 2020; Xiaohua et al, 2022; Yu et al, 2022). For example, the knockdown of NAP1L1 expression significantly reduced cell proliferation and cell cycle transformation in vitro and in vivo by disturbing hepatoma‐derived growth factor and c‐Jun signaling pathways that induce the expression of cell cycle factors such as cyclin D1 (Liu, Zhang, et al, 2022; Liu et al, 2021; Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These reports showed that NAP1L1 has multiple functions beyond the nucleosome assembly function. Such functions include proliferation, migration, invasion, and even thrombopoiesis (Freitag & Schwertz, 2022;Liang et al, 2022;Nagashio et al, 2020;Xiaohua et al, 2022;Yu et al, 2022).…”
Section: Analysis Of Rna-seq Data Of Nap1l1 Kd Cellsmentioning
confidence: 99%
“…Moreover, studies have reported that diabetes is associated with the incidence, mortality, and progression of various cancers 6,[11][12][13] . Experimental studies [14][15][16] have revealed that hyperglycemia per se, rather than the common risk factors between diabetes and cancer, worsens cancer. Hyperglycemia renders cancer cells more aggressive by exerting metabolic and oxidative stresses [16][17][18] .…”
mentioning
confidence: 99%